Energy absorption of thin-walled beams with a pre-folded origami pattern - Ma, J; You, Z (Elsevier, 2013)

(untitled)
This paper presents a novel energy absorption structure known as the origami beam. It is made from a shallow curved thin-walled beam of square cross section whose surface is pre-folded according to an origami pattern. Numerical simulation of the quasi-static lateral collapse of the origami beam shows that two new collapse modes, referred to as the longitudinal folding mode and the mixed mode both of which feature large magnitude of plastic deformation along the entire beam, can be triggered in the beam, leading to higher energy absorption and lower peak force than those of conventional ones.